Strategic Planning for Transportation Systems in Developing Countries Case Study: Damascus, Syria - ALYOUSEF, DUHA (İstanbul Kültür Üniversitesi, 2025)
This study focuses on the strategic planning of transportation in Damascus, Syria, over a five-year period. The city's transportation system reflects a mix of historical depth and modern-day complexity, shaped by ongoing urban growth and political challenges. Today, Damascus struggles with traffic congestion, limited public transit options, and aging infrastructure. The aim of this research is to analyze the current planning approach, identify key weaknesses, and suggest practical strategies for improvement. The study also emphasizes the importance of linking transportation planning with broader goals such as sustainability, economic development, and social well-being. By addressing both the existing issues and potential opportunities, the research hopes to offer guidance for more efficient and inclusive mobility solutions in the coming years.
Keywords: Strategic Planning